Analisis Kepraktisan Buku Ilmiah Populer Keanekaragaman Jenis Ikan Berbasis Penelitian Sebagai Bahan Pengayaan Mata Kuliah Zoologi Vertebrata Konsep Ikan - Riya Irianti; Mahrudin Mahrudin (Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Popular scientific book is one of the teaching materials which is used in the learning process. adn connect information with community. Popular scientific book is very useful for students. It helps to enhance students’ insight and knowledge about the material which is being studied by the students. Especially, the material which are based on local potential. The existence of popular scientific books with local potential support students. Therefore, by knowing the objects in their environment, students will understand more deeply about the study of material because the objects of study presented and can be seen on a daily basis. The purpose of this study to analyze the practicality of BIP on the diversity of fish species as an enrichment material for the Vertebrate Zoology Course in Fish Concept. The research method is descriptive quantitative, to find information on the practicality of teaching materials which is scrutinized based on the research results, using the Research and Development. The subjects of practicality data are 7 students and 10 students for student responses. The results of this research shows that the teaching materials compiled based on the results of the study were obtained for readability in the very good category and student responses stated that popular scientific books were practical to use.